EVALUASI FORMATIF PROGRAM BANTUAN SEMBAKO PANGAN DI KECAMATAN CILINCING KOTA JAKARTA UTARA - Nisa, Ayi Fakhrotun; Fawzi, Indra Lestari (Social Welfare Study Program, 2022)
Abstract. This research study the program of the Non Cash Food Assistance Program (BSP) in Cilincing District, North Jakarta Administration City. This research is a formative evaluation study with an approach that aims to describe the implementation process of the Non Cash Food Assistance Program (BSP) in Cilincing District, Central Jakarta City. The results of this study indicate that in general, the implementation of the Non Cash Food Assistance Program (BSP) in Cilincing District, North Jakarta is exceptional, this is shown by collecting data on potential beneficiaries through surveys, implementing education and outreach to all stakeholders, implementing Prosperous Family Cards (KKS) through the door to door method, assistance provided through e-warong as well as the use of assistance provided by Beneficiary Families (KPM) such as processing basic necessities to meet daily needs. Meanwhile, there are some problems that need to adressed by the authorities such as deception from e-warong in the transaction of the BSP which sell item to KPM outside the guidelines book. In addition, there is time delay on the fund transfer to the KPM and also